Along‐Strike Variation in the Initiation Timing of the North‐Trending Rifts in Southern Tibet as Revealed From the Yadong‐Gulu Rift. Issue 7 (1st July 2022) - Bian, Shuang; Gong, Junfeng; Zuza, Andrew V.; Yang, Rong; Chen, Lin; Ji, Jianqing; Yu, Xiangjiang; Tian, Yihong; Yu, Zhiquan; Cheng, Xiaogan; Lin, Xiubin; Chen, Hanlin
Abstract: A key issue in the Cenozoic evolution of the Tibetan plateau is the geodynamic drivers for north‐trending rifting in southern Tibet. Recent studies have demonstrated an eastward propagation pattern for rift initiation, but the along‐strike variations remain poorly resolved. Two models that predict different north‐south rift kinematics include northward underthrusting or southward tearing of the Indian lithospheric slab, predicting a northward or southward propagation trend of individual rifts along strike, respectively. The Yadong‐Gulu rift (YGR) is an ideal case to investigate this issue due to its long strike length (∼500 km) and location above proposed slab‐tear structures. Here, we compile constraints on both rift initiation and acceleration, and report new apatite fission track and (U‐Th)/He thermochronological data along the southern segment of YGR. Our main findings are as follows. First, the rifts west of the YGR initiated simultaneously along strike, which we suggest is at odds with predictions of either slab‐tear or slab‐underthrusting models. However, most of these rifts show a northward younging pattern in rift acceleration, which may be governed by low‐angle Indian slab underthrusting released by slab tearing. Second, the initiation timing of the Yadong rift is constrained at ∼13–11 Ma. Combined with published constraints along strike, we demonstrate a clear northward propagation in rift initiation along the YGR. This kinematic pattern may be affected by its orientation of the most oblique northeast‐trending among all rift systems or the outward expansion of the Himalayan arc. Plain Language Summary: The Himalayan‐Tibetan orogen is undergoing active east‐west extension under the continuous compression of the colliding Indo‐Eurasia continents. This extension is manifested by a series of northward oriented (north‐striking) rifts in southern Tibet, the geodynamics of which is critical in revealing the Cenozoic evolution of the Tibetan Plateau. Despite the importance, their development pattern along strike has not been well understood, leaving the mechanisms that emphasize their along‐strike propagation poorly tested, such as the southward slab tearing and northward slab underthrusting models. They predict a southward or northward propagation of rifting along strike, respectively. Therefore, the along‐strike propagation process of individual rifts constitutes the key factor in distinguishing the two mechanisms. In this study, we adopted thermochronological techniques to constrain the propagation of the Yadong‐Gulu rift (YGR) that has the longest strike length. The results suggest that the YGR youngs northward, which is contrary to the situations of each rift system to its west that initiated nearly coevally along strike. This implies that the onset of north‐trending rifts should not be significantly affected by geodynamic process in N‐S direction through either slab tearing or underthrusting, while the northward younging trend of YGR is controlled largely by its oblique striking. Key Points: Initiation timing of Yadong‐Gulu rift youngs northward (Yadong at ∼13–11 Ma), but each rift system to its west initiated nearly coevally along strike Slab tearing released subducting slab and activated slab underthrusting that causes northward rifting acceleration Extraordinary earlier initiation of the Yadong rift was related to its most oblique NE‐trending or outward expansion of the Himalayan arc